2017
DOI: 10.1007/s11682-017-9672-4
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations in college football players: a longitudinal diffusion tensor imaging study

Abstract: The aim of this study was to evaluate longitudinal changes in the diffusion characteristics of brain white matter (WM) in collegiate athletes at three time points: prior to the start of the football season (T1), after one season of football (T2), followed by six months of no-contact rest (T3). Fifteen male collegiate football players and 5 male non-athlete student controls underwent diffusion MR imaging and computerized cognitive testing at all three timepoints. Whole-brain tract-based spatial statistics (TBSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 63 publications
0
42
1
Order By: Relevance
“…Although our 6-month data collection period would have occurred at least 3 months post-season for all athletes, Bazarian et al (2014) demonstrated that changes in DTI metrics seen at the end of the season persisted for at least 6 additional months in collegiate athletes. Mayinger et al (2017), however, found normalization of DTI metrics to pre-season levels after 6 months in their sample of collegiate football players. Further investigation is required to determine if WM changes persist or are reversible with extended periods of non-exposure (off season).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although our 6-month data collection period would have occurred at least 3 months post-season for all athletes, Bazarian et al (2014) demonstrated that changes in DTI metrics seen at the end of the season persisted for at least 6 additional months in collegiate athletes. Mayinger et al (2017), however, found normalization of DTI metrics to pre-season levels after 6 months in their sample of collegiate football players. Further investigation is required to determine if WM changes persist or are reversible with extended periods of non-exposure (off season).…”
Section: Discussionmentioning
confidence: 84%
“…Findings of increased diffusion in the months following the season, when athletes are presumably less active, are in concordance with these findings. In support of the potential effect of repetitive head impact exposure, increases in diffusion have been demonstrated from preseason to postseason evaluations in nonconcussed college athletes(Mayinger et al, 2017;McAllister et al, 2014). Furthermore, McAllister et al (2014) demonstrated that increased MD in the corpus callosum at postseason correlated with head impact metrics.…”
mentioning
confidence: 95%
“…Relation to previous investigations. A variety of previous investigations into the effects of sports participation, repetitive head impacts and white matter tissue properties of athletes have used the diffusion tensor (DTI) model (Bahrami et al, 2016;Basser et al, 1994;Bazarian et al, 2014;Burzynska et al, 2016;Chang et al, 2015;Chun et al, 2015;Churchill et al, 2017aChurchill et al, , 2017bDavenport et al, 2016aDavenport et al, , 2016bDavenport et al, , 2014Deng et al, 2018;Duru and Balcioglu, 2018;Gajawelli et al, 2013;Hänggi et al, 2015Hänggi et al, , 2010Jäncke et al, 2009;Koerte et al, 2012;Kuzminski et al, 2018;Lao et al, 2015;Marchi et al, 2013;Mayinger et al, 2018;McAllister et al, 2014;Merchant-Borna et al, 2016;Myer et al, 2018Myer et al, , 2016aMyer et al, , 2016bPark et al, 2015;Saghafi et al, 2018;Schlaffke et al, 2014;Schranz et al, 2018;Sollmann et al, 2018;Stamm et al, 2015;Yuan et al, 2018) . The studies investigating the effects of elite sports participation commonly report lower fractional anisotropy (FA) and higher mean diffusivity (MD) between athletes and non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…amygdala, hippocampus, basal ganglia) white matter. A paucity of articles have studied differences in either major (Bahrami et al, 2016;Bazarian et al, 2014;Churchill et al, 2017aChurchill et al, , 2017bDavenport et al, 2016aDavenport et al, , 2016bKoerte et al, 2012;Kuzminski et al, 2018;Mayinger et al, 2018;McAllister et al, 2014;Merchant-Borna et al, 2016;Saghafi et al, 2018;Sollmann et al, 2018;Stamm et al, 2015;Yuan et al, 2018) or cortical and subcortical (Mayer et al, 2017) white matter between collision sport participants and controls (i.e., non-athletes, non-collision sport athletes, within-subject longitudinal), but few have looked at all three to fully characterize the effects of sports participation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 25 youth football players found an association between cumulative head impact exposure and microstructural changes in certain white matter tracts over a single season in the absence of concussion [17]. Similarly, a longitudinal study of collegiate football players found white matter changes on diffusion-tensor MRI following one season of play in the absence of concussion; however, these athletes underwent repeat imaging after six months of rest from contact activity, and the white matter changes had returned to baseline [18]. At this time, there is not enough evidence to correlate changes in white matter to the subsequent development of neurodegenerative disease or functional deficits, especially in young athletes.…”
Section: Neuroimagingmentioning
confidence: 96%